2008
DOI: 10.1161/atvbaha.107.156745
|View full text |Cite
|
Sign up to set email alerts
|

Oxidant Generation Predominates Around Calcifying Foci and Enhances Progression of Aortic Valve Calcification

Abstract: Objective-We hypothesized that reactive oxygen species (ROS) contribute to progression of aortic valve (AV) calcification/stenosis. Methods and Results-We investigated ROS production and effects of antioxidants tempol and lipoic acid (LA) in calcification progression in rabbits given 0.5% cholesterol diet ϩ10 4 IU/d Vit.D 2 for 12 weeks. Superoxide and H 2 O 2 microfluorotopography and 3-nitrotyrosine immunoreactivity showed increased signals not only in macrophages but preferentially around calcifying foci,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
162
0
6

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(184 citation statements)
references
References 41 publications
16
162
0
6
Order By: Relevance
“…A recent study demonstrated that increased ROS generation, particularly H 2 O 2 , is predominately located around calcifying foci, which potentiates aortic valve calcification progression (54). By contrast, H 2 O 2 has been shown to have adverse effects on osteogenic differentiation of MC3T3-E1 cells, a pre-osteoblastic cell line (53), and primary bone marrow stromal cells and calvarial osteoblast precursors (55).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that increased ROS generation, particularly H 2 O 2 , is predominately located around calcifying foci, which potentiates aortic valve calcification progression (54). By contrast, H 2 O 2 has been shown to have adverse effects on osteogenic differentiation of MC3T3-E1 cells, a pre-osteoblastic cell line (53), and primary bone marrow stromal cells and calvarial osteoblast precursors (55).…”
Section: Discussionmentioning
confidence: 99%
“…Low concentrations of H 2 O 2 increase ALP activity and potentiate the progression of aortic valve calcification [22,23] . The levels of expression of mRNAs for OPN and OCN were significantly greater in ROS-treated human dental pulp cells [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical, 1 histological, 2 and animal 3 studies support the coincidence of osteoporosis and vascular calcification and suggest that processes in vascular calcification are similar to those of bone remodeling. 4 Hence, a better molecular understanding of common processes of these comorbidities may lead to more efficient therapeutic strategies against these age-related diseases.…”
mentioning
confidence: 97%